Countries experiences: review of district health management in developing and low developing countries - S. G., Auwal; K. K., Kaur; A. M., Salma; T., Kay; A. I., Kamal; S. A., Ismail; I., Suriani; B. Z., Huda (Community Health Society Malaysia, 2016)
A strong healthcare system is characterized by efficient health service delivery, adequate manpower and resource generation, a sustainable financing system and good governance. District healthcare system is the one closest to the people and its performance in relation to resource allocation impacts directly on the community health status. Over the years, many of the developed nations have learned to prioritize it mainly because it remains the most ideal way of improving population health through activities of general health promotion, disease prevention and provision of basic medical care. In the developing countries, achievement of district health system is not uniform and even among countries with comparable income per capita, wide variations exist. While some have attained a commendable population health status by strengthening their district healthcare systems by redoubling government’s commitment, enhancing resource production, encouraging fairness in healthcare financing and adopting development-oriented health policies, many others are facing healthcare challenges from lack of political will, limited resource allocation and shortage of both manpower and service infrastructure. For these countries, there is an urgent need to transform the district health system so that new and existing health problems can be dealt with decisively and more efficiently. This will require a renewed commitment from the state governments, reprioritizing and readjustment of present health programs, an inter-sectorial collaboration that involves all relevant stakeholders including the communities, and a renewed investment in sustainable health policies that deliver maximum impact at minimal cost.